A Comparative Assessment of the Creativity in Adolescents Across Two Categories of Schools in Pithoragarh, Central Himalaya - Nautiyal, Anil Kumar; Negi, Prabha (JOURNAL OF INDIAN EDUCATION, 2011)
The present study, conducted among the adolescent students of Class XII attempts a comparative assessment of creativity (i) in girls versus boys, (ii) in students enrolled in government run schools versus those enrolled in private schools, and (iii) across different economic groups of students. Adolescents, in the age group between 15 and 18 years, and studying in the 12thstandard were selected across six different schools: Private run-3 and government funded-3, located within the township of Pithoragarh, Uttarakhand. Altogether 178 adolescents, represented by 103 boys and 75 girls were selected randomly. Measurement of potential creativity was done through Passi tests of creativity. In an overall appraisal of difference between sexes in ability, achievement, and readiness, the differences were very slight, and certainly not sufficient to warrant the fact that creativity differs across the sex. However, a sharp difference is conspicuous in the functioning of creativity of the adolescents, enrolled in private run with those enrolled in government run schools, with creativity level being significantly more in adolescents enrolled in the former. Creativity shows a positive correlation with the socio- economic status of the family, irrespective of the sex of the student. It is strongly felt that if the potential of creativity is to be harnessed, a requisite motivating environment, which boosts up their self -concept and achievement motivation, remains obligatory.